THE DIALECTIC OF THE NATIONAL AND THE LOCAL: INDIAN EDUCATIONAL PRACTICE - Yanxi Liu, (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This study investigates the tension between national policy and local practice in achieving educational justice in India. It aims to develop a more effective governance model by introducing the concept of scale-sensitivity. Methodology: A comparative case study analysis of the national Right to Education (RTE) Act and the grassroots Akshar Model is conducted, guided, and refined through Nancy Fraser’s 3R (redistribution, recognition, representation) framework. Findings: The research reveals that the RTE Act’s centralized power is effective for redistribution but weak on local recognition and representation. Conversely, the Akshar Model excels in recognition and representation at the grassroots level but lacks scalable redistribution. The findings demonstrate that centralized and localized models are not opposites but necessary complements. Research Outcomes: The primary outcome is the proposal for a synergistic state-grassroots ecosystem. The core theoretical contribution is the refinement of Fraser’s framework with the scale-sensitivity principle, arguing that different dimensions of justice are optimally pursued at different governance levels. It offers a more nuanced analytical tool for India and similar diverse nations to foster educational justice. Future Scope: Future research should explore the institutional channels and policy mechanisms required to operationalize this synergistic ecosystem in practice.